ANALISIS RISIKO USAHATANI CABAI MERAH BESAR (Capsicum annuum L.) DI DESA SUKALAKSANA KECAMATAN BANYURESMI KABUPATEN GARUT - Raini Hurul Misqi; Tuti Karyani (Universitas Galuh Ciamis, 2020)
Sukalaksana Village is one of the areas in the Banyuresmi District of Garut Regency, which is known as a red chili producer. Although it has highly economic value, red chili is one of agricultural commodities that have farming risks, both production risk, cost and income. The research objectives are (1) identify the source of farming risk, (2) analyze the level of farm risk (production risk, cost risk, and income risk), and (3) determine the farmer's strategy of overcoming a farm risk. The analysis model uses a descriptive analysis and risk analysis (a coefficient of variation). The results showed that there were opportunities for production, cost, and income risk of conducting red chili farming. Production risk is caused by weather conditions and pests that attack red chili plants. The cost risk is caused by the high costs incurred by farmers in the use of production facilities due to the high price of chemical fertilizers and pesticides. Revenue risk is caused by the quality of production due to pests and diseases, high costs of production facilities, and price fluctuations. The strategy carried out by farmers in dealing with production risks is to maintain the plants well but still use chemicals. The strategy for dealing with costing risk is to borrow money from the dealer or family. But so far the farmers have not made a strategy to deal with income risk because the current risk of income is the accumulation of production risk and chili cost and price risk.